A Simple One-Pot Procedure for the Synthesis of 1,2,4-Triazolo[1,5-a]pyrid-ines via Pseudo Five-Component Reactions Catalyzed by Molecular Iodine - Alizadeh, Abdolali; Saberi, Vahid; Mokhtari, Javad (Synlett, 2013)
In this paper we report the synthesis of the 1,2,4-triazolo[1,5-a]pyridine ring system. The reaction between benzylidenehydrazines, dialkyl acetylenedicarboxylates, benzaldehydes, and malononitrile proceeds in EtOH at reflux in the presence of molecular iodine as catalyst in good to excellent yields.
Keywords: benzylidenehydrazine; dialkyl acetylenedicarboxylate; benzaldehyde; malononitrile; 1,2,4-triazolo[1,5-a]pyridine; catalyst; iodine; multicomponent reaction